Monozygotic twins discordant for recessive dystrophic epidermolysis bullosa phenotype highlight the role of TGF-β signalling in modifying disease severity. (5th March 2014) - Odorisio, Teresa; Di Salvio, Michela; Orecchia, Angela; Di Zenzo, Giovanni; Piccinni, Eugenia; Cianfarani, Francesca; Travaglione, Antonella; Uva, Paolo; Bellei, Barbara; Conti, Andrea; Zambruno, Giovanna; Castiglia, Daniele
Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is a genodermatosis characterized by fragile skin forming blisters that heal invariably with scars. It is due to mutations in the COL7A1 gene encoding type VII collagen, the major component of anchoring fibrils connecting the cutaneous basement membrane to the dermis. Identical COL7A1 mutations often result in inter- and intra-familial disease variability, suggesting that additional modifiers contribute to RDEB course. Here, we studied a monozygotic twin pair with RDEB presenting markedly different phenotypic manifestations, while expressing similar amounts of collagen VII. Genome-wide expression analysis in twins' fibroblasts showed differential expression of genes associated with TGF-β pathway inhibition. In particular, decorin, a skin matrix component with anti-fibrotic properties, was found to be more expressed in the less affected twin. Accordingly, fibroblasts from the more affected sibling manifested a profibrotic and contractile phenotype characterized by enhanced α-smooth muscle actin and plasminogen activator inhibitor 1 expression, collagen I release and collagen lattice contraction. These cells also produced increased amounts of proinflammatory cytokines interleukin 6 and monocyte chemoattractant protein-1. Both TGF-β canonical (Smads) and non-canonical (MAPKs) pathways were basally more activated in the fibroblasts of the more affected twin. The profibrotic behaviour of these fibroblasts was suppressed by decorin delivery to cells. Our data show that the amount of type VII collagen is not the only determinant of RDEB clinical severity, and indicate an involvement of TGF-β pathways in modulating disease variability. Moreover, our findings identify decorin as a possible anti-fibrotic/inflammatory agent for RDEB therapeutic intervention.